(untitled) (XXI Century. Spanish Literature and Culture, 2008)
Hidalgo Calle, Lola. Elementos populares y existencialistas en la obra del poeta Rafael Montesinos. Newark: Juan de la Cuesta Hispanic Monographs, 2006. Ofelia Ferrán. Working through Memory. Writing and Remembrance in Contemporary Spanish Narrative. Lewisburg: Bucknell University Press, 2007. V.V.A.A. A Companion to the Twentieth-Century Spanish Novel.Woodbridge: Támesis, 2008.